Assessment Strategies, Instructional Resources, Science Course Teaching Methods and Acquisition of Employability Skills by Potential Science Graduates: The Lecturers’ Perspective - Ogunniran, Olukemi Omolola; Makinde, Olayinka Babayemi (Journal of Digital Learning and Education, 2024)
The study examines the interconnectedness of assessment strategies, instructional resources, and science course teaching methods relating to employability skills acquisition by potential science graduates from the lecturers’ perspective. The study utilised a research survey design. A sample of 371 was drawn from the population of science lecturers in universities in South-west using a multi-stage sampling technique. This involved purposive, stratified, and quota sampling techniques. A well-structured questionnaire was used to collect data analysed using descriptive statistics (multiple bar charts) and inferential statistics of correlation and regression analyses. The key findings of the study showed that instructional resources [instructional material, physical facilities, and human resources], science course teaching methods, and assessment strategies had joint significant predictions on employability skills acquisition. This implies that these variables must be adequately provided for improved acquisition of employability skills by students. Also, lecturers’ understanding of students’ key employability skills revealed low ratings of information technology, initiative, leadership, problem-solving, and adaptability skills of students. The study recommends that higher education administrators should strive to provide instructional materials, physical facilities and human resources as instructional resources to implement excellent teaching techniques and assessment strategies. The study concludes that lecturers should consciously seek self-upgrade and improve teaching techniques and assessment strategies.